Study on the uncertainty of geological drilling parameters by the uncertainty theory - Sheng, Yanan; Zhichuan Guan (Kuwait Journal of Science, 2019)
The drilling geological parameters reflect the integrated nature of the oil and gas geological basic data. The knowledge of them are important to avoid the drilling risk. Due tothe complexity ofpetroleum geology, the incompleteness of the logging or seismic data, the precision ofthe mathematical model and other issues, the true value of drilling geological parameters can be hardly obtained. Based on the theory of stratigraphic science and uncertainty, the method of describing the uncertainty of the drilling geological parameters was established. Firstly, the drilling geological parameters interpreted by logging or seismic data in the same stratum were regarded as the measured sample. Then the probability distribution or interval range of drilling geological parameters at each measurement point were determined based on this sample. Finally the uncertainty interval of parameters of drilling geological parameters along with the well depth can be obtained. The results of example showed that the uncertain description of the drilling geological parameters was more relevant with the practical engineering.